Travel Restrictions in Siargao: An Intervention for the Island’s Long-Term Sustainability - Dellova, Rovena I.; Capadosa, Khrystal; Dangcalan, Janela A.; Descartin, Aliyah D.; Jatol, Rheem; Hernandez, Michelleana S.; Virrey, John Victor C. (Journal of Governance Risk Management Compliance and Sustainability, 2024)
An overwhelming influx of tourists to a destination can create massive pressure. Siargao, a tourism-first island known as "Asia's Best Island" and the "Surfing Capital of the Philippines", is one of the favorite spots and has captivated the hearts of tourists around the world. This study investigated the efficacy of travel restrictions to ensure the island’s long-term sustainability. This descriptive research, using a quantitative approach, utilized snowball sampling. Data were gathered from 400 respondents from the National Capital Region. The findings revealed that Siargao is popularly known as one of the top attractions in the Philippines, and respondents are aware that excessive tourism may lead to site deterioration. Restrictions could be an effective intervention to achieve island conservation. Stakeholders can make a substantial contribution to conservation efforts by closely observing tourist demand and behavior to incorporate the current travel restrictions into strategies and, thereby, prevent traffic and destruction of natural sites when visitation levels return to normal. These restrictions could be an effective environmental conservation intervention; therefore, implementing these travel limitations is an effective way to ensure long-term gains that contribute to Siargao’s conservation goals. Considering this additional intervention, a thorough intervention, and its impact will greatly help determine the significance of the improvement. Thus, this pioneering study provides supporting statements to help Siargao rise to the top Philippine destination and ensure the long-term sustainability of tourism.